2022
DOI: 10.3389/fcell.2022.981696
|View full text |Cite
|
Sign up to set email alerts
|

Bicaudal-C Post-transcriptional regulator of cell fates and functions

Abstract: Bicaudal-C (Bicc1) is an evolutionarily conserved RNA binding protein that functions in a regulatory capacity in a variety of contexts. It was originally identified as a genetic locus in Drosophila that when disrupted resulted in radical changes in early development. In the most extreme phenotypes embryos carrying mutations developed with mirror image duplications of posterior structures and it was this striking phenotype that was responsible for the name Bicaudal. These seminal studies established Bicc1 as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Null mutation of the encoding gene causes defective oogenesis and results in a tumorous germline phenotype ( Jones et al, 1996 , Jones and Inouye, 1996 ). Bicaudal-C (Bicc1) is a conserved embryonic RNA-binding protein with three KH domains that regulates Drosophila development by binding to the 3′ UTRs of target mRNAs thereby reducing their stability and repressing their translation ( Dowdle et al, 2022 ). Maternal knockdown and rescue experiments in Drosophila have demonstrated that KH domains of Bicc1 are required to regulate embryogenesis ( Dowdle et al, 2019 ).…”
Section: Eukaryotic Kh Domain Proteinsmentioning
confidence: 99%
“…Null mutation of the encoding gene causes defective oogenesis and results in a tumorous germline phenotype ( Jones et al, 1996 , Jones and Inouye, 1996 ). Bicaudal-C (Bicc1) is a conserved embryonic RNA-binding protein with three KH domains that regulates Drosophila development by binding to the 3′ UTRs of target mRNAs thereby reducing their stability and repressing their translation ( Dowdle et al, 2022 ). Maternal knockdown and rescue experiments in Drosophila have demonstrated that KH domains of Bicc1 are required to regulate embryogenesis ( Dowdle et al, 2019 ).…”
Section: Eukaryotic Kh Domain Proteinsmentioning
confidence: 99%